Shoulder Infrared Thermography in Chronic Rotator Cuff Tears - Temperature Assessment and Variation in Affected and Non-Affected Shoulders - Ricardo Vardasca, PhD, ASIS, FRPS (2019)
Background Chronic Rotator Cuff Tears (RCT) are a common and disabling condition. Local tissue changes may be assessed by Infrared Thermography (IRT). It was hypothesized that IRT might provide useful information for diagnosis of chronic RCT, yielding lower local skin temperatures. Methods Included patients consisted of adults with chronic primary RCT (> 3 months). Demographics and occupation were recorded. An IRT protocol was used, at rest and after exercise, for both affected and contralateral shoulder. Frontal, dorsal and lateral views were used, and Regions of Interest (ROI's) were defined in the topography of the main rotator cuff tendons. Three independent observers assessed temperature, and concordance analysis was performed. Significant temperature variation was defined as 0.5 ℃. Results 52 patients - 16 males and 36 females - were evaluated, mean age 56 ± 1.3 years old. Inter-observers' concordance was greater than 95%. A slight decrease in temperature was verified after the exercise protocol in affected and contra-lateral shoulders, but this was less than 0.5 ℃. Comparing the skin temperature of affected shoulders and contralateral temperatures, no significant differences were revealed, both at rest or after exercise. Conclusion The obtained results demonstrated IRT as highly reproducible. A small decrease in skin temperature after exercise has been related to peripheral vasoconstriction, and this was confirmed in both affected and non-affected shoulders. Nevertheless, it was expected on affected shoulders a lower baseline and after exercise skin temperatures, which was not confirmed, as no significant difference was found between groups. As such, the role of IRT as complimentary mean of diagnosis is yet to be established in RCT.